P6 Managing acute pulmonary embolism in the outpatient setting: initial experiences and outcomes in a UK district general hospital. (2nd December 2011) - Corcoran, J P; Park, J E S; Goode, C; Davies, C W H
Abstract : Introduction and Objectives: Outpatient (OP) management of low risk cases of pulmonary embolism (PE) can be as effective as inpatient (IP) management and reduce length of stay (LOS) (1). Concerns exist regarding the safety of this strategy, with a wide range of adverse outcomes reported (2). In our hospital a treatment pathway was implemented to identify low risk individuals diagnosed with PE suitable for OP management, based on the European Society of Cardiology PE Guidelines (2008) (Abstract P6 figure 1 ). The aim of this study was to retrospectively review all cases of acute PE in a 6-month period, to determine appropriateness of management as OP and assess LOS, venous thromboembolism (VTE) recurrence and anticoagulation related adverse events. Methods: Episodes of PE occurring between January and June 2010 were identified through clinical coding (ICD-10: I26). Clinical notes were reviewed and data collected for LOS, time to diagnostic investigation, risk stratification (troponin, echocardiography and adverse clinical features), IP/OP management, recurrence of VTE, bleeding events, respiratory clinic follow-up and mortality. Results: 102 cases were identified of which 90 had acute PE. 81 sets of clinical notes were available. 24 (29.6%) patients were managed as OP. This group was younger than those treated as IP (59.30±3.84 vs 64±2.12, p<0.05). The LOS was significantly shorter for OP: (1.87±0.27 vs 8.79±0.77 days; p<0.0001). There were no episodes of recurrent VTE or bleeding events at 90 days in either group, and only one readmission for anticoagulation related events (high INR; IP group). Three patients (3.7%) died within 90 days (1 from sepsis, 1 from metastatic carcinoma and 1 from congestive cardiac failure). We identified a number of patients with low risk who were not treated as OP for a various reasons. All patients with OP management were subsequently followed by Respiratory team. Conclusions: Out patient management of diagnosed PE in a carefully selected group is practical, safe and decreases LOS using existing OP DVT services. The use of risk stratification assists identification of safe OP management.